Diffusion of Innovation Theory Adaptation in Genomic-Based Product Marketing Strategy - Levanya Martina Marbun (Eduvest - Journal of Universal Studies, 2024)
With the rise of preventative healthcare needs after the COVID-19 pandemic, tanyaDNA, a genomics company in Indonesia, seeks to introduce Lifestyle and Pharmacogenomic Testing. This study explores using Diffusion of Innovation Theory to create a targeted marketing strategy for this new service. There's a lack of awareness and affordability concerns surrounding the test, along with a knowledge gap between the company, healthcare professionals, and the target market. The research aims to assess the theory's applicability, bridge these understanding gaps, and promote successful integration of the test into Indonesian healthcare. This can inform marketing strategies for other genomics companies looking to expand beyond COVID-19 testing. The study focuses on the JABODETABEK area of Indonesia and utilizes surveys and interviews to gather data. The findings can help bridge the gap between product creators and target markets, especially regarding the perspectives of key healthcare professionals.